Growth And Characterization Of Vertically Aligned Zno Nanorods Synthesized By Chemical Bath Deposition For Uv Photodetector Applications - Shabanniarami, Reza (2013)
The objectives of this study are to grow and characterize the structural, optical, and electrical properties of aligned ZnO nanorods, and to develop ultraviolet (UV) photodetectors using these ZnO nanorod arrays grown with optimized growth parameters. The study employed two different substrates for growing ZnO nanorod arrays; first, flexible polyethylene naphthalate (PEN) seeded ZnO and second, porous silicon (PS) seeded ZnO. Well-aligned ZnO nanorod arrays were grown on flexible PEN substrates at a low temperature by using the chemical bath deposition (CBD). The control of the diameter, length, density, and optical and structural properties of the ZnO nanorod arrays were systematically investigated by modifying the growth parameters, including the precursor concentration and growth duration. Vertically aligned ZnO nanorod arrays grown using a 0.050 M precursor concentration and 5 h growth duration had diameters ranging from 10 nm to 40 nm and exhibited the sharpest and most intense UV peak in the room temperature photoluminescence (PL) results compared with other samples. Next, high quality ZnO nanorod arrays were synthesized through the optimization of precursor concentration and growth duration by using CBD method on PS substrates, which were prepared via the photo electrochemical etching (PECE) method. The aligned ZnO nanorods grew perpendicular to the PS substrates and had average diameters and lengths ranging from 13 nm to 69 nm and from 85 nm to 208 nm, respectively.